The mRNA Expression of PTEN, LEF1, JAK3, LC3 and p62/SQSTM1 Genes in Patients with Chronic Myeloid Leukemia - Lak, Elahe Razmara; Tamaddon, Gholamhossein; Ramzi, Mani; Ranjbaran, Reza; Abedi, Elham; Sharifzadeh, Sedigheh (Cardiovascular & hematological agents in medicinal chemistry, 2023)
Chronic myeloid leukemia (CML) is a progressive myeloproliferative disorder resulting from forming a chimeric BCR-ABL gene. The proteins derived from this gene can affect some genes from various signaling pathways such as PI3K/AKT/Wnt/catenin/JAK/Stat involved in proliferation, differentiation, cell death, and genes related to autophagy. Imatinib is the first-line treatment for CML patients, with durable and proper responses in Iranian children and adult CML patients. Hence, we aimed to evaluate the mRNA expression of some selected key genes from those pathways in patients with CML before and under treatment. In the case-control study, the mRNA expression of PTEN, LEF1, JAK3, LC3 and p62 genes were measured in 51 CML patients (6 patients before treatment and 45 patients under treatment with imatinib mesylate) and 40 healthy controls using the Real-time PCR method. The mRNA expression of PTEN and P62 were significantly higher in newly diagnosed patients than in controls (P<0.0001 and P = 0.0183, respectively), while the expression of the LC3 gene was significantly lower in the untreated newly diagnosed group than in control subjects (P = 0.0191). The expression level of PTEN, LEF1, JAK3 and P62 genes were significantly decreased in patients under treatment than in the group before treatment (P = 0.0172, P = 0.0002, P = 0.0047 and P = 0.0038, respectively). A positive correlation was seen between the gene expression of P62 and BCR-ABL in the patients under treatment (r 0529, P = 0.016). Our findings showed that the changes in expression of these genes were related to the patient's treatment. Due to the key role of these genes in proliferation, differentiation and tumor suppression, it is proposed that these genes may be helpful for follow-up of treatment in CML patients.